Integrated policies to improve the energy–water–food system nexus to achieve the SGDs - Bollino, Carlo Andrea; Anbumozhi, Venkatachalam; Babu, Suresh Chandra; Eiji, Yamaji; Galeotti, Marzio (T20, 2020)
The challenges posed by the water–food–energy nexus have been well documented. Demand for all three of these crucial elements of human growth is increasing, driven by a rising global population, rapid urbanization, changing diets, and economic growth. However, an integrated approach to technological, institutional, and policy innovation is missing in the context of achieving the Sustainable Development Goals (SDGs). The proposed strategy in this policy brief relies on three pillars: (1) improvements in the measurement and promotion of better policies and investments for integrated energy, water, and food security; (2) the assessment of the institutional constraints and determinants of the inequalities between leading and lagging countries and the speed of adjustment that will bring convergence among them; and (3) the facilitation of renewable energy technologies as an environmentally sustainable supply of energy, with substantial positive spill-over effects in the water and food sectors. The suggestion is to promote policies to (1) facilitate which determinants are best suited to enhance the convergence of policy process, such as economic diversification, subsidy removal, and liberalization through a multisectoral approach; and (2) support increasing electricity access using alternative sources of energies in remote rural areas in Asia, Africa, and Latin America through integrated Official Development Assistance (ODA) and Foreign Direct Investment (FDI).